Three amino acid changes in PB1-F2 of highly pathogenic H5N1 avian influenza virus affect pathogenicity in mallard ducks - Marjuki, Henju (2010)
Despite reports that the PB1-F2 protein contributes to influenza virus pathogenicity in the mouse model, little is known about its significance in avian hosts. In our previous study the A/Vietnam/1203/04 (H5N1) wild-type virus (wtVN1203) was more lethal to mallard ducks than a reverse genetics (rg)–derived VN1203. In search of potential viral factors responsible for this discrepancy, we found that synonymous mutations (SMs) had been inadvertently introduced into 3 genes of the rgVN1203 (rgVN1203/SM-3). Of 11 SMs in the PB1 gene, 3 resided in the PB1-F2 open reading frame, caused amino acid (aa) substitutions in the PB1-F2 protein, and reduced virus lethality in mallard ducks. The wtVN1203 and recombinant viruses with repairs to these 3 aa’s (rgVN1203/R-PB1-F2) or with repairs to all 11 SMs (rgVN1203/R-PB1) were significantly more pathogenic than rgVN1203/SM-3. In cultured cells repairing 3 mutations in PB1-F2 increased viral polymerase activity and expression levels of viral RNA.